(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Immune checkpoint inhibitors (ICIs) can cause a wide spectrum of immune-related adverse events, including encephalitis. To date, no prospective randomised controlled trials examining the patient characteristics, treatment and outcomes of ICI-associated encephalitis have been published. Therefore, we aimed to review case reports and to provide recommendations for the management of ICI-associated encephalitis. METHODS A literature search using Google Scholar and PubMed was performed in December 2019. Published case reports and case series of ICI-associated encephalitis were reviewed, and a case series from the Limmattal Hospital in Schlieren, Switzerland was added. The results are presented as numbers and medians (ranges). RESULTS Five different ICIs caused encephalitis in the 47 patients included in this case series. Nivolumab was the most frequently involved drug (27/47, 57%). The median time between treatment and onset of symptoms was 65 (4–630) days. Patients presented with rapidly evolving confusion, reduced level of consciousness, headache, seizures and focal neurological deficits. A total of 19 out of the 44 (43%) magnetic resonance imaging (MRI) scans performed revealed findings suggestive of encephalitis. No specific electroencephalogram (EEG) pattern consistent with encephalitis was found, but epileptiform discharges were detected in 7/20 (35%) of all tested patients. Typical findings of cerebrospinal fluid (CSF) analysis were pleocytosis, elevated protein levels and normal glucose concentrations. Forty-four out of 47 (94%) patients received corticosteroids. Intravenous immunoglobulins (IVIG), rituximab and plasma exchange therapy were less frequently prescribed. Nine out of 47 (19%) patients died during the index hospitalisation. CONCLUSIONS Encephalitis should be suspected in patients treated with ICIs who present with rapidly evolving confusion. Blood tests, CSF analysis, cerebral MRI and an EEG should be performed. Therapy with intravenous corticosteroids is recommended. Steroid unresponsiveness is rare and should lead to a review of the diagnosis. Alternative treatment options are IVIG, plasma exchange therapy and rituximab.